Alloreactive cytotoxic T lymphocyte immunotherapy treatment of a patient with metastatic prostate cancer: A case report. Issue 24 (June 2018) - Shi, Junfeng; Chen, Yi; Chen, Yuetong; Shen, Yunzhu; Zhao, Huanyu; Sun, Hui; Chen, Jinfei
Abstract: Rationale: Cytotoxic T lymphocyte (CTL) immunotherapy is an autologous cellular immune therapy that has been approved for treating patients with malignant tumors. However, there is still limited information regarding the impact of CTL on metastatic prostate cancer (PC) patients with bone metastatic lesions. Patient concerns: An 82-year-old male patient complained of interrupted urination, urination pain, and significant dysuria on November 24, 2014. Transurethral resection of the prostate (TURP) and postoperative pathological examination showed prostatic adenocarcinoma, and a SPECT/CT scan demonstrated multiple bone metastases. In addition, prostate specific antigen (PSA) and free PSA (FPSA) levels were 54.54 μg/mL and 2.63 μg/mL, respectively, at the beginning of treatment. Diagnoses: The man was diagnosed with prostatic adenocarcinoma and multiple bone metastases. Interventions: The patient received 30 cycles of alloreactive CTL (ACTL) immunotherapy regularly. Outcomes: Over the course of the 2-year treatment, the PC patient exhibited diminished bone metastasis accompanied by a marked reduction of serum PSA and FPSA from 54.54 and 2.63 μg/ml to 0.003 and <0.006 μg/ml, respectively. Lessons: Our clinical observations demonstrate that CTL immunotherapy is a viable treatment option for PC patients, particularly those with bone metastatic lesions and high serum levels of PSA and FPSA.